A role for age-associated alterations in esophageal epithelium in eosinophilic esophagitis-associated fibrosis - Klochkova, Alena; Fuller, Annie D.; Miller, Riley; Karami, Adam L.; Panchani, Surali R.; Natarajan, Shruthi; Mu, Anbin; Jackson, Jazmyne L.; Klein-Szanto, Andres J.; Muir, Amanda B.; Whelan, Kelly A. (Frontiers in Allergy, 2022)
Subepithelial fibrosis occurs in a subset of eosinophilic esophagitis (EoE) patients and is associated with esophageal stricture. While mechanisms driving EoE fibrosis remain incompletely understood, findings from experimental systems support roles for epithelial-fibroblast crosstalk in this type of tissue remodeling. The current paradigm presents EoE as a progressive fibrostenotic disease in which aged patients develop fibrosis as a function of disease chronicity. In the current study we provide evidence that altered epithelial biology in the aging esophagus may also contribute to EoE-associated fibrosis. We find that induction of EoE inflammation in young and aged mice using the MC903/Ovalbumin protocol for the same time period results in increased lamina propria thickness uniquely in aged animals. Additionally, epithelial cells from aged mice less efficiently limit fibroblast contractility in collagen plug contraction assays compared to those from their young counterparts. Finally, to identify potential mechanisms through which aged esophageal epithelial cells may stimulate fibrotic remodeling, we perform cytokine array experiments in young and aged mice. These studies are significant as identification of age-associated factors that contribute to fibrotic remodeling may aid in the design of strategies toward early detection, prevention, and therapy of fibrostenotic EoE.